Lithium-rich manganese-based positive electrode material with controllable oxygen vacancy and preparation method of lithium-rich manganese-based positive electrode material
Through sol-gel method and swing sintering technology, lithium-rich manganese-based positive electrode material with few lattice oxygen vacancy and rich surface oxygen vacancy was prepared, which solved the voltage attenuation and structural instability of the material during the circulation process, and achieved the High capacity retention and low voltage attenuation effects.
Patent Information
- Application Number
- CN202411329639.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials have severe voltage attenuation and structural instability during the cycle, resulting in capacity decay and initial Coulombic efficiency, and it is difficult to effectively control the oxygen vacancy distribution of the surface and body phase.
The sol-gel method combined with swing sintering technology and induced surface oxygen vacancies are used to prepare lithium-rich manganese-based positive electrode materials with few lattice oxygen vacancies and rich surface oxygen vacancies. By adjusting the sintering temperature gradient and the use of surface treatment agents, the Oxygen vacancies distribution, thereby improving the electrochemical properties of the material.
A capacity retention rate of 85% and a significant reduction in voltage attenuation to 3.81mV/cycle in 150 cycles was achieved, significantly improving the cycle stability and electrochemical properties of the material.
Smart Images

Figure CN119191383A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a positive electrode material capable of increasing the capacity of a lithium-rich manganese-based positive electrode material and reducing voltage decay. Background Art
[0002] Lithium-ion batteries have shown great application prospects in various electronic products due to their high specific capacity, cycle stability and safety. With the growing demand for high-performance lithium-ion batteries, improving the reversible capacity and energy output of the cathode has attracted much attention. However, the discharge specific capacity of commercial cathodes is generally less than 250 mAh g -1 To this end, lithium-rich manganese-based (LRM) layered oxides are considered as next-generation cathode materials due to their ultrahigh specific capacity within a unique framework. However, several significant drawbacks, including severe voltage fade and unsatisfactory structural stability, have hindered their commercialization.
[0003] The activation of LRM during the initial charge process leads to the irreversible release of oxygen, forming oxygen vacancies. Lattice oxygen is continuously consumed in subsequent cycles, which helps to produce more OVs. Unfortunately, the increase in lattice oxygen loss leads to structural degradation and phase transition (from layered structure to spinel structure), resulting in gradual voltage degradation, severe capacity decay and low initial Coulombic efficiency. However, during the material preparation process, the electrochemical performance can be improved by pre-generating surface oxygen vacancies, thereby inducing an oxygen-deficient environment and reducing the generation of O2.
[0004] Therefore, how to effectively control the distribution of oxygen vacancies on the surface and bulk of the lithium-rich manganese-based cathode material, thereby increasing the capacity of the lithium-rich manganese-based cathode material and reducing its voltage decay during the cycle is the main problem that technicians in this field want to solve for lithium-rich manganese-based cathode materials.
[0005] Based on the above reasons, this application is filed. Summary of the Invention
[0006] Based on the above reasons, in view of the problems or defects in the prior art, the object of the present invention is to provide a method for preparing a lithium-rich manganese-based positive electrode material with controllable oxygen vacancies, so as to solve or at least partially solve the above technical defects in the prior art. In order to synthesize electrode materials with better electrochemical performance, the present invention uses a sol-gel method, combined with a rocking sintering technology and an induced surface oxygen vacancy technology, to synthesize a lithium-rich manganese-based positive electrode material with few lattice oxygen vacancies and rich surface oxygen vacancies. The prepared cathode has a capacity retention rate of 85%, and at 0.5C, the voltage decay is significantly reduced to 3.81mV / cycle in 150 cycles.
[0007] In order to achieve the above-mentioned first object of the present invention, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a lithium-rich manganese-based positive electrode material with controllable oxygen vacancies, characterized in that the method specifically comprises the following steps:
[0009] S1. preparing a metal salt solution containing Li, Mn, Ni and Co ions, a chelating agent solution and an alkaline solution;
[0010] S2. Under continuous stirring, the chelating agent solution is added dropwise to the metal salt solution, and the pH is adjusted by adding an alkaline solution dropwise. The mixed solution is continuously stirred at 80° C. until a wet gel is formed;
[0011] S3, drying the wet gel, pre-calcining for a certain period of time, and then sintering at a temperature gradient of 700-900° C. and 900-700° C. to obtain a sample;
[0012] S4. The sample is mixed evenly with a surface treatment agent and reacted at a suitable temperature for a certain period of time under argon atmosphere. After thorough washing with water and ethanol and drying, a lithium-rich manganese-based layered oxide with few lattice oxygen vacancies and abundant surface oxygen vacancies is obtained.
[0013] Preferably, the metal salt is at least one of metal acetate, nitrate and oxalate.
[0014] Preferably, the chelating agent is at least one of citric acid, oxalic acid, ethylenediaminetetraacetic acid, malonic acid and polyvinylpyrrolidone.
[0015] Preferably, the alkaline solution is at least one of ammonia water, sodium hydroxide, sodium carbonate and ethanolamine.
[0016] Preferably, the molar ratio of the chelating agent to the metal salt is 1-3:1.
[0017] Preferably, in step S2, the pH value is adjusted to 5-7.
[0018] Preferably, in step S3, the pre-calcination temperature is 400-600° C., and the holding time is 4-8 hours.
[0019] Preferably, in step S3, the heating and cooling rates at the temperature gradients of 700-900°C and 900-700°C are between 0.1-0.3°C / min.
[0020] Preferably, in step S4, the surface treatment agent is one or more of ammonium bicarbonate, ammonium fluoride, urea, ammonium nitrate and ammonium oxide.
[0021] Preferably, in step S4, the mixing ratio of the surface treatment agent to the sample is 4-6:1.
[0022] Preferably, in step S4, the surface treatment agent and the sample are mixed and kept at a temperature of 180-250° C. for 8-15 hours.
[0023] The second object of the present invention is to provide a lithium-rich manganese-based positive electrode material prepared by the above-mentioned method, wherein the lithium-rich manganese-based positive electrode material has a spinel phase.
[0024] The third object of the present invention is to provide the use of the lithium-rich manganese-based positive electrode material prepared by the above method in lithium-ion batteries.
[0025] The roles played by the raw materials of the present invention are as follows:
[0026] Metal acetates: Metal acetates have high solubility in water, which enables them to form uniform solutions during the sol-gel process; metal acetates are relatively chemically stable in solution and are not prone to side reactions; the acetate ions in metal acetates can effectively coordinate with metal ions to form stable metal complexes.
[0027] Citric acid: Contains three carboxyl groups (-COOH) and one hydroxyl group (-OH), which can react with metal ions (such as Li + 、Mn 2+ This strong chelation helps to evenly disperse the metal ions and prevent them from local precipitation in the solution, thereby improving the uniformity of the precursor solution.
[0028] Ammonia: Ammonia is a weak base, and the pH value of the solution can be precisely controlled by adjusting its concentration and addition amount. When dissolved, ammonia generates ammonia gas and water without introducing additional metal ions or other impurities. The ammonia molecules provided by ammonia can react with transition metal ions (such as Mn 2+ 、Ni 2+ etc.) to form coordination compounds, further stabilizing the metal ions in the solution and preventing local precipitation.
[0029] The reaction mechanism involved in the present invention is as follows:
[0030] 1. The present invention uses a sol-gel method to mix and fully contact transition metal ions in water at the atomic level, and then forms a uniformly dispersed and stable chelate by adding citric acid and ammonia water.
[0031] 2. The swing sintering method not only meets the requirements of regulating crystal nucleation during the heating process of the positive electrode material, but also takes into account the regulation of crystal growth during the cooling process. At the same time, it optimizes the volume and surface structure of the material, thereby reducing the inherent oxygen vacancy concentration of the lithium-rich manganese base and stabilizing the lattice oxygen.
[0032] 3. The ammonia and carbon dioxide generated by the thermal decomposition of ammonium bicarbonate corrode the surface of the material, thereby generating abundant oxygen vacancies on the surface of the material.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention improves the calcination process. Although there have been reports of non-isothermal sintering techniques such as swinging and ammonia-induced surface oxygen vacancy methods, no attempt has been made to integrate these methods into material preparation. The present invention introduces the concept of controllable oxygen vacancies for the first time.
[0035] 2. The present invention synthesizes a layered oxide Li with few lattice oxygen vacancies and rich surface oxygen vacancies. 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2. It effectively suppresses the voltage decay of the lithium-rich manganese-based cathode. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 It is the X-ray diffraction pattern of the lithium-rich manganese base prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0038] Figure 2 These are SEM morphology images of lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0039] Figure 3 This is the O1s spectrum of the lithium-rich manganese-based positive electrode material prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0040] Figure 4 This is the EPR spectrum of the lithium-rich manganese-based positive electrode material prepared in Example 1 and Comparative Examples 1 and 2 of the present invention.
[0041] Figure 5 This is a first cycle charge and discharge curve diagram of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 of the present invention at a rate of 0.1C.
[0042] Figure 6 1 is a discharge capacity curve of the lithium-rich manganese-based positive electrode materials prepared in Example 1 of the present invention and Comparative Examples 1 and 2 after 150 cycles at a rate of 1C.
[0043] Figure 7 This is an average voltage decay graph of the lithium-rich manganese-based positive electrode materials prepared in Example 1 of the present invention and Comparative Examples 1 and 2 after 150 cycles at a rate of 1C. DETAILED DESCRIPTION
[0044] Based on the information contained in this application, it will be readily apparent to those skilled in the art that various changes can be made to the precise description of the present invention. It should be understood that the scope of the present invention is not limited to the defined processes, properties, or components, as these embodiments and other descriptions are provided only to illustrate specific aspects of the present invention.
[0045] In order to better understand the present invention and not to limit the scope of the present invention, all numbers used in this application to express amounts, percentages, and other numerical values should be understood to be modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0046] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following examples are all conventional methods in the art unless otherwise specified.
[0047] Example 1
[0048] The present embodiment provides a lithium-rich manganese-based cathode material with controllable oxygen vacancies and a preparation method thereof. The method specifically comprises the following steps: preparing a lithium-ion lithium-rich manganese-based cathode material NS-LRM according to the following method:
[0049] S1. Metal acetates (Li, Mn, Ni, and Co), a citric acid chelating agent (a molar ratio of citric acid to metal acetate of 2), and aqueous ammonia were weighed in stoichiometric proportions and dissolved in deionized water to form a 2 M metal acetate solution, a 2 M citric acid solution, and a 0.5 M aqueous ammonia solution;
[0050] S2. While stirring continuously, add the citric acid solution dropwise to the metal acetate solution, then add ammonia solution dropwise to adjust the pH to 7 to ensure that the metal ions are evenly dispersed in the solution. Then, place the mixed solution in an 80°C water bath and stir continuously until a wet gel is formed.
[0051] S3. After drying the wet gel, pre-calcining it at 500°C for 6 hours, and then sintering it at a temperature gradient of 700-900°C and 900-700°C at a heating and cooling rate of 0.15°C / min. After the temperature drops to 700°C, it is naturally cooled to 20°C to obtain a lithium-rich manganese-based positive electrode material with few lattice oxygen vacancies;
[0052] S4. The obtained sample was mixed evenly with an appropriate amount of ammonium bicarbonate (the molar ratio of sample to ammonium bicarbonate was 1:5) and then placed in a closed reactor filled with Ar. The mixture was then reacted at 200°C for 12 hours. After being thoroughly washed with water and ethanol, the modified sample was dried in an oven to obtain a lithium-rich manganese-based layered oxide (NS-LRM) with low lattice oxygen vacancies and abundant surface oxygen vacancies.
[0053] Example 2
[0054] The present embodiment provides a lithium-rich manganese-based cathode material with controllable oxygen vacancies and a preparation method thereof, wherein the method specifically comprises the following steps: preparing the lithium-ion lithium-rich manganese-based cathode material according to the following method:
[0055] S1. Metal acetates (Li, Mn, Ni, and Co), a citric acid chelating agent (a molar ratio of citric acid to metal acetate of 1.5), and aqueous ammonia were weighed in stoichiometric proportions and dissolved in deionized water to form a 2 M metal acetate solution, a 2 M citric acid solution, and a 0.5 M aqueous ammonia solution;
[0056] S2. While stirring continuously, add the citric acid solution dropwise to the metal acetate solution, then add ammonia solution dropwise to adjust the pH to 6 to ensure that the metal ions are evenly dispersed in the solution. Then, place the mixed solution in an 80°C water bath and stir continuously until a wet gel is formed.
[0057] S3. After drying the wet gel, pre-calcining it at 500°C for 6 hours, and then sintering it at a temperature gradient of 700-900°C and 900-700°C at a heating and cooling rate of 0.15°C / min. After the temperature drops to 700°C, it is naturally cooled to 20°C to obtain a lithium-rich manganese-based positive electrode material with few lattice oxygen vacancies;
[0058] S4. The obtained sample was mixed evenly with an appropriate amount of ammonium bicarbonate (the molar ratio of sample to ammonium bicarbonate was 1:5) and then placed in a closed reactor filled with Ar. The mixture was then reacted at 200°C for 12 hours. After being thoroughly washed with water and ethanol, the modified sample was dried in an oven to obtain a lithium-rich manganese-based layered oxide with low lattice oxygen vacancies and abundant surface oxygen vacancies.
[0059] Example 3
[0060] The present embodiment provides a lithium-rich manganese-based cathode material with controllable oxygen vacancies and a preparation method thereof, wherein the method specifically comprises the following steps: preparing the lithium-ion lithium-rich manganese-based cathode material according to the following method:
[0061] S1. Metal acetates (Li, Mn, Ni, and Co), a citric acid chelating agent (a molar ratio of citric acid to metal acetate of 2), and aqueous ammonia were weighed in stoichiometric proportions and dissolved in deionized water to form a 2 M metal acetate solution, a 2 M citric acid solution, and a 0.5 M aqueous ammonia solution;
[0062] S2. While stirring continuously, add the citric acid solution dropwise to the metal acetate solution, then add ammonia solution dropwise to adjust the pH to 6 to ensure that the metal ions are evenly dispersed in the solution. Then, place the mixed solution in an 80°C water bath and stir continuously until a wet gel is formed.
[0063] S3. After drying the wet gel, pre-calcining it at 500°C for 6 hours, and then sintering it at a temperature gradient of 700-900°C and 900-700°C at a heating and cooling rate of 0.2°C / min. After the temperature drops to 700°C, it is naturally cooled to 20°C to obtain a lithium-rich manganese-based positive electrode material with few lattice oxygen vacancies;
[0064] S4. The obtained sample was mixed evenly with an appropriate amount of ammonium bicarbonate (the molar ratio of sample to ammonium bicarbonate was 1:5) and then placed in a closed reactor filled with Ar. The mixture was then reacted at 200°C for 12 hours. After being thoroughly washed with water and ethanol, the modified sample was dried in an oven to obtain a lithium-rich manganese-based layered oxide with low lattice oxygen vacancies and abundant surface oxygen vacancies.
[0065] Comparative Example 1
[0066] The difference between Comparative Example 1 and Example 1 lies in that the calcination process is different.
[0067] Li was prepared as follows 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 body material P-LRM:
[0068] S1. Metal acetates (Li, Mn, Ni, and Co), a citric acid chelating agent (a molar ratio of citric acid to metal acetate of 2), and aqueous ammonia were weighed in stoichiometric proportions and dissolved in deionized water to form a 2 M metal acetate solution, a 2 M citric acid solution, and a 0.5 M aqueous ammonia solution;
[0069] S2. While stirring continuously, add the citric acid solution dropwise to the metal acetate solution, then add ammonia solution dropwise to adjust the pH to 7 to ensure that the metal ions are evenly dispersed in the solution. Then, place the mixed solution in an 80°C water bath and stir continuously until a wet gel is formed.
[0070] S3. After drying overnight, the gel was pre-calcined at 500 °C for 6 h and sintered at 900 °C in air for 12 h. The obtained sample was labeled P-LRM.
[0071] Comparative Example 2
[0072] Comparative Example 2 is different from Example 1 in that there is no subsequent surface treatment step of ammonium bicarbonate after calcination.
[0073] S1. Metal acetates (Li, Mn, Ni, and Co), a citric acid chelating agent (a molar ratio of citric acid to metal acetate of 2), and aqueous ammonia were weighed in stoichiometric proportions and dissolved in deionized water to form a 2 M metal acetate solution, a 2 M citric acid solution, and a 0.5 M aqueous ammonia solution;
[0074] S2. While stirring continuously, add the citric acid solution dropwise to the metal acetate solution, then add ammonia solution dropwise to adjust the pH to 7 to ensure that the metal ions are evenly dispersed in the solution. Then, place the mixed solution in an 80°C water bath and stir continuously until a wet gel is formed.
[0075] S3. After drying the wet gel, pre-calcining it at 500°C for 6 hours, and then sintering it at a temperature gradient of 700-900°C and 900-700°C at a heating and cooling rate of 0.15°C / min. After the temperature dropped to 700°C, it was naturally cooled to 20°C to obtain the lithium-rich manganese-based cathode material S-LRM with few lattice oxygen vacancies.
[0076] Comparative Example 3
[0077] Comparative Example 3 is the same as Comparative Example 1, except that in step S2, the pH is adjusted to 8.
[0078] Product performance testing
[0079] The crystal structure test of the lithium-rich manganese-based materials prepared in Example 1 and Comparative Examples 1 and 2 was carried out. The test results are as follows: Figure 1As shown in the figure, it can be seen that except for the diffraction peak between 20° and 25°, the other peaks are strongly correlated with the layered α-NaFeO2 structure, which is the LiMn6 superlattice diffraction of the monoclinic C2 / m Li2MnO3 phase. The split peaks of (006) / (012) and (018) / (110) are obvious in all samples, indicating that the samples have a typical layered structure and good hexagonal order. The intensity ratio of peak (003) to peak (104) usually indicates that Li + and Ni 2+ The degree of mixing in the Li layer. The ratios for the three samples were 1.665, 1.844, and 1.804, respectively, indicating that the Li-Ni mixing content in all samples was very low. The ratios for the S-LRM and NS-LRM samples were higher, indicating that the SNS technique can effectively improve the Li-Ni mixing. In addition, a (104) facet shoulder peak associated with the spinel phase was found in the NS-LRM sample.
[0080] The SEM morphology of the lithium-rich manganese-based materials prepared in Example 1 and Comparative Examples 1 and 2 was observed, and the results were as follows: Figure 2 All samples showed a nearly cubic structure and formed agglomerates. The particle size distribution of the particle agglomerates was relatively uniform and narrow, with a particle size range of 300 to 500 nm.
[0081] The O1s spectra of the lithium-rich manganese-based materials prepared in Example 1 and Comparative Examples 1 and 2 were analyzed. Figure 3 All samples have three fitting peaks at 533.39eV, 531.53eV and 529.66eV, which belong to OH - ions, O - or O2 2- Defective oxygen ions and O 2- lattice oxygen ions. In NS-LRM, the defective oxygen moves to 531.36eV with lower binding energy. It has been reported that the O1s peak moves to the direction of lower binding energy after NH3 treatment, which is due to the generation of oxygen vacancies on the surface of the material. The relative contents of lattice oxygen in P-LRM and S-LRM are 68.96% and 77.70%, respectively, indicating that the SNS technology has successfully stabilized the lattice oxygen. In addition, compared with S-LRM, the surface defective oxygen content of NS-LRM is higher (27.78%), which proves the introduction of oxygen vacancies on the surface of NS-LRM.
[0082] The EPR spectra of the lithium-rich manganese-based materials prepared in Example 1 and Comparative Examples 1 and 2 were analyzed, and the results were as follows: Figure 4The g-factors of all samples are approximately 2.005, which is related to the presence of oxygen vacancies. It is worth noting that the S-LRM sample exhibits the lowest EPR response, indicating that there are fewer OVs species in the S-LRM, which is consistent with the XPS results.
[0083] The first cycle charge and discharge curves of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2 at a rate of 0.1C were analyzed. Figure 5 As shown in Figure 2, a long plateau region at ~4.5V during the first charge process is associated with the oxygen release process. The capacity below 4.4V reflects the Li + Reversible deintercalation from LiMO2 is accompanied by cationic redox (Ni and Co redox couple). The initial discharge capacities of the P-LRM, S-LRM, and NS-LRM samples are 255.8, 260.7, and 276.9 mAh g, respectively. -1 , and the coulombic efficiency is 78.71%, 79.27% and 79.58% respectively. The reason why NS-LRM has a higher capacity and initial coulombic efficiency is that the spinel component exists on the surface of NS-LRM, which inhibits the continuous activation of Li2MnO3 and is beneficial to the + diffusion.
[0084] The discharge specific capacity curves of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 after 150 cycles at a rate of 1C were analyzed. Figure 6 The NS-LRM sample showed only marginal capacity decay even after 150 cycles, with the capacity remaining at approximately 170 mAh g -1 For P-LRM, the capacity decreases significantly with continued cycling, decreasing to only 120.6 mAh g at the 150th cycle. -1 This demonstrates the superiority of our work in controlling the surface oxygen vacancy concentration. Stabilizing lattice oxygen can effectively improve the cycling stability, and on this basis, the introduction of surface oxygen vacancies improves the specific capacity.
[0085] The average discharge voltage curves of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 after 150 cycles at a rate of 1C were analyzed. Figure 7As shown. The voltage decay value of NS-LRM is only 3.81mV / cycle, which is lower than 5.63mV / cycle of P-LRM and 4.14mV / cycle of S-LRM. It is worth noting that all samples show a slight downward trend in the first 50 cycles. However, after the 50th cycle, the voltage degradation rate in the P-LRM sample accelerates, indicating that the structural change intensifies. These results confirm that precise control of oxygen vacancies can effectively suppress the phase transition of the layered structure in the NS-LRM sample, thereby reducing the voltage decay.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based positive electrode material with controllable oxygen vacancies, characterized in that: The method specifically comprises the following steps: S1. preparing a metal salt solution containing Li, Mn, Ni and Co ions, a chelating agent solution and an alkali solution; S2. Under continuous stirring, the chelating agent solution is added dropwise to the metal salt solution, and the pH is adjusted by adding an alkali solution dropwise, and the mixed solution is continuously stirred at 80° C. until a wet gel is formed; S3, drying the wet gel, pre-calcining for a certain period of time, and then sintering at a temperature gradient of 700-900° C. and 900-700° C. to obtain a sample; S4, the sample is mixed with the surface treatment agent evenly, and reacted for a certain period of time at a suitable temperature filled with argon. After being thoroughly washed with water and ethanol and dried, a lithium-rich manganese-based layered oxide with few lattice oxygen vacancies and abundant surface oxygen vacancies is obtained.
2. The method according to claim 1, characterized in that The metal salt is at least one of metal acetate, nitrate and oxalate; the chelating agent is at least one of citric acid, oxalic acid, ethylenediaminetetraacetic acid, malonic acid and polyvinylpyrrolidone.
3. The method according to claim 1, characterized in that The alkaline solution is at least one of ammonia water, sodium hydroxide, sodium carbonate and ethanolamine, and the pH value is adjusted to 5-7.
4. The method according to claim 1, characterized in that The molar ratio of the chelating agent to the metal salt is 1-3:
1.
5. The method according to claim 1, characterized in that In step S3, the pre-calcination temperature is 400-600°C, and the holding time is 4-8h.
6. The method according to claim 1, characterized in that In step S3, the heating and cooling rates at the temperature gradients of 700-900°C and 900-700°C are 0.1-0.3°C / min.
7. The method according to claim 1, characterized in that In step S4, the surface treatment agent is one or more of ammonium bicarbonate, ammonium fluoride, urea, ammonium nitrate and ammonium oxide, and the mixing ratio of the surface treatment agent to the sample is 4-6:
1.
8. The method according to claim 1, characterized in that In step S4, the surface treatment agent and the sample are mixed and kept at a temperature of 180-250°C for a time of 8-15 hours.
9. The lithium-rich manganese-based positive electrode material prepared by the method according to any one of claims 1 to 8, characterized in that: The lithium-rich manganese-based positive electrode material has a spinel phase.
10. Use of the lithium-rich manganese-based positive electrode material prepared by the method according to any one of claims 1 to 8 in lithium-ion batteries.
Citation Information
Cited By
Manganese-oxygen double-vacancy lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery
CN120463251A
Oxygen-vacancy-rich multi-surface-defect nickel oxide positive electrode material for thermal battery and preparation method
CN122224841A
